PENYELESAIAN SENGKETA BATAS WILAYAH KABUPATEN PASANGKAYU DENGAN KABUPATEN DONGGALA DALAM PERSPEKTIF KEADILAN DAN KEPASTIAN HUKUM - Mulyadi, Mulyadi (TADULAKO MASTER LAW JOURNAL, 2024)
The research results obtained conclusions 1). The dispute over the territorial boundaries of Pasangkayu Regency and Donggala Regency has gone through a non-litigation and litigation resolution process through judicial institutions. In this case, mediation or facilitation was carried out 4 (four) times by the Ministry of Home Affairs, until the Supreme Court issued Decision Number: 5 P/HUM/2023 dated March 23 2023, which declared the Minister of Home Affairs Regulation Number 60 of 2018 concerning Regional Boundaries of Pasangkayu Regency void. West Sulawesi Province with Donggala Regency, Central Sulawesi Province dated July 18 2018. As for legal action, in the form of a judicial review of the regional formation law at the Constitutional Court, there is still an opportunity. However, it is known that the Constitutional Court in several recent decisions considers territorial boundary disputes within the Republic of Indonesia not to be a constitutional issue that deserves to be tested by the Constitutional Court. Rather, it is the authority of the government in stages, namely the authority of the governor, or the Minister of Home Affairs. 2). The legal consequences of the Supreme Court's decision Number: 5 P/HUM/2023 dated 23 March 2023 on the administration of regional government in border areas, have consequences for: Aspects of legal certainty in the administration of regional government; Aspects of public service certainty, which must be carried out by the West Sulawesi Provincial Government and Pasangkayu Regency, in providing basic services to residents of the community; and Fulfillment of the political rights of citizens, both voters and those elected (candidates), by providing services and building polling stations in the implementation of election and regional election contestation.